Functional expression, localization, and biochemical characterization of thioredoxin glutathione reductase from air-breathing magur catfish, Clarias magur - Koner D.; Nag N.; Kalita P.; Padhi A.K.; Tripathi T.; Saha N. (My University, 2025)
The glutathione (GSH) and thioredoxin (Trx) systems regulate cellular redox homeostasis and maintain antioxidant defense in most eukaryotes. We earlier reported the absence of gene coding for the glutathione reductase (GR) enzyme of the GSH system in the facultative air-breathing catfish, Clarias magur. Here, we identified three thioredoxin reductase (TrxR) genes, one of which was later confirmed as a thioredoxin glutathione reductase (TGR). We then characterized the novel recombinant TGR enzyme of C. magur (CmTGR). The tissue-specific expression of the txnrd genes and the tissue-specific activity of the TrxR enzyme were analyzed. The recombinant CmTGR is a dimer of ~133 kDa. The protein showed TrxR activity with 5,5′-diothiobis (2-nitrobenzoic acid) reduction assay with a Km of 304.40 μM and GR activity with a Km of 58.91 μM. Phylogenetic analysis showed that the CmTGR was related to the TrxRs of fishes and distantly related to the TGRs of platyhelminth parasites. The structural analysis revealed the conserved glutaredoxin active site and FAD- and NADPH-binding sites. To our knowledge, this is the first report of the presence of a TGR in any fish. This unusual presence of TGR in C. magur is crucial as it helps maintain redox homeostasis under environmental stressors-induced oxidative stress. © 2023 Elsevier B.V.